Rethinking justice beyond human rights. Anti-colonialism and intersectionality in the politics of the Palestinian Youth Movement. Issue 3 (27th May 2021) - Welchman, Lynn; Zambelli, Elena; Salih, Ruba
ABSTRACT: This article discusses the politics of the Palestinian Youth Movement (PYM) – a contemporary social movement operating across a number of Arab and western countries. Unlike analysis on the Arab Uprisings which focused on the national dimension of youth activism, we explore how the PYM politics fosters and upholds an explicitly transnational anti-colonial and intersectional solidarity framework, which foregrounds a radical critique of conventional notions of self-determination based on state-framed human rights discourses and international law paradigms. The struggle becomes instead framed as an issue of justice, freedom and liberation from interlocking forms and hierarchies of oppression.